2014
DOI: 10.1063/1.4892409
|View full text |Cite
|
Sign up to set email alerts
|

Surface structures of In-Pd intermetallic compounds. II. A theoretical study

Abstract: The (110) surface of the InPd intermetallic compound and the In-Pd surface alloy properties are investigated in the framework of the density functional theory, within the projector augmented plane-wave method. Surface segregation is calculated to be energetically unfavorable at stoichiometric InPd(110) surfaces, while indium antisites are shown to segregate to the surface in off-stoichiometric InPd(110) systems. Concerning surface alloys obtained by burying In-doped Pd layers in Pd(111), we demonstrated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
4
8
0
Order By: Relevance
“…This agrees with the theoretical prediction of a negative mixing enthalpy for the In x Pd 1 − x solid solution in the dilute In limit reported in Ref. 25. In the low coverage regime (θ ≤ 2 MLE), the LEED patterns are consistent with the formation of three rotational domains of InPd(110) on top of the Pd(111) substrate.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This agrees with the theoretical prediction of a negative mixing enthalpy for the In x Pd 1 − x solid solution in the dilute In limit reported in Ref. 25. In the low coverage regime (θ ≤ 2 MLE), the LEED patterns are consistent with the formation of three rotational domains of InPd(110) on top of the Pd(111) substrate.…”
Section: Discussionsupporting
confidence: 91%
“…This was interpreted as a consequence of the larger thermodynamic driving force for Ga-Pd compound formation compared to Zn-Pd based on the calculated cohesive energies. The onset alloying temperature was not determined in the present study but is lower or equal to 300 K. This is consistent with the cohesive energy calculated for the InPd compound (−3.57 eV/atom) 25 which is intermediate between that of PdGa (−3.9 eV/atom) 19,40 and ZnPd (−3.0 eV/atom). 41 Concerning the orientation of the surface alloys, we found that the cubic 1:1 InPd NSIP adopts a (110) orientation with respect to the Pd(111) substrate whereas the 1:1 tetragonal ZnPd NSIP adopts a (111) orientation.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations